Due date assignment and convex resource allocation scheduling with variable job processing times. Issue 12 (17th June 2016) - Sun, Lin-Hui; Cui, Kai; Chen, Ju-hong; Wang, Jun
Abstract : This is a study of a earliness and tardiness sequencing and scheduling problem on a single machine. The processing time for job depends on its position in a sequence, its starting time, and its allocation of non-renewable resource. For three due date assignment methods i.e. the common due date, the slack due date and the unrestricted due date our goal is to find the optimal schedule, due dates, and resource allocations of jobs. We prove that three versions of the problem can be solved in polynomial time, respectively.